Habenaria parviflora (Orchidaceae), extension of its austral distributional limit and new synonymy - Sanguinetti, Agustin (2015)
An extension of the austral distributional limit of Habenaria parviflora Lindl. and a new record for the orchid flora of Buenos Aires province is reported on the basis of specimens collected from the northwestern hills of the Tandilia System. Habenaria uruguayensis Garay is found to be a synonym of H. parviflora based on studies of original material, protologues and previous bibliography. A lectotype is designated for H. parviflora.